Hyperresponsiveness to inflammatory stimulation in human neuronal-like cells from patients with inflammation-associated depression - Schillo, Susanne Elisa; Schiweck, Carmen; Aichholzer, Mareike; Yotova, Anna Y.; Tsengenbayar, Tsendmaa; Edwin Thanarajah, Sharmili; Reif, Andreas; Freudenberg, Florian (Frontiers in Psychiatry, 2025)
IntroductionChronic low-grade inflammation has been associated with the development and progression of depression. However, its impact on neuronal development and connectivity remains poorly understood. In this study, we investigated how chronic and acute inflammation may influence early neurite development in neuronal-like cells (monocyte-derived neuronal-like cells, MDNCs).MethodsCirculating monocytes were obtained from healthy controls (HC, n = 5), patients with major depression (MD, n = 4), patients with depression and elevated peripheral inflammatory markers (MD-INF, n = 4) and patients with schizophrenia (SZ, n = 5). Monocytes were transdifferentiated into MDNCs and either left untreated (CTRL) or exposed to lipopolysaccharide (LPS, 100 ng/mL) to induce an acute inflammatory response. Neurite morphology was quantified using MAP2 immunofluorescence staining and microscopic analysis.ResultsTransdifferentiation rates were significantly higher in MD-INF cultures compared with HC, MD and SZ. Sholl analysis demonstrated that MD-INF MDNCs treated with LPS exhibited a significantly greater neurite ending radius than MD and SZ cells or MD-INF under control conditions. Similarly, MD-INF cells treated with LPS showed more Sholl intersections compared with SZ cells treated with LPS and MD-INF cells under control conditions. Furthermore, the average neurite length of MD-INF cells treated with LPS exceeded that of MD and SZ cells treated with LPS and MD-INF cells under control conditions.DiscussionThese findings suggest a hyperresponsive phenotype to inflammatory stimulation in vitro in early neurons from patients with depression and elevated peripheral inflammation. Our results may provide novel insights into how inflammation could influence neurodevelopmental processes relevant to depression and may serve as a model for further investigations regarding targeted interventions.